A learning approach to the ethical organization. Issue 2 (2014) - George E. Smith; Kathleen J. Barnes; Claudia Harris
<x xml:space="preserve"> Abstract </x> Purpose – This review explores the parallels between the characteristics of learning organizations and the characteristics of ethical organizations. Design/methodology/approach – A review of the literature was conducted to examine the characteristics of learning organizations and those that encourage and support ethical behavior. Findings – There are significant parallels between the characteristics of learning organizations and those of ethical organizations. These include leadership, culture, communication, systems thinking, and problem‐solving orientation, which are important in creating learning organizations and in encouraging ethical behavior. These parallels encourage social network stimulation, acceptance of new ideas, open discussion, the ability to disagree without rancor, a lessening of hierarchy, employees seeing themselves as part of a larger whole. All of these elements create an environment wherein organizational members are able to contend with and resolve ethical problems. Practical implications – When endeavoring to foster an ethical organizational environment, managers can be aware of the benefits of creating a learning organization, as the two correspond closely. Additionally, managers in learning organizations can leverage this capacity to enhance ethical decision making and behavior. Originality/value – Research on learning organizations has often centered on their value in encouraging innovation and on strategies for implementing the changes needed to establish them. This paper identifies and discusses the parallels between the characteristics of learning organizations and ethical organizations. This is an area that has not been directly explored in the extant literature. <ack> <x xml:space="preserve"> Acknowledgements </x> The authors gratefully acknowledge Dr Claudia Harris (12/7/1947‐10/31/13) for the foundational work for this article. Claudia's unique insights and world view will be missed. </ack>